Seroprevalence of peste des petits ruminants in sheep and goats managed under pastoral and agro-pastoral systems - Julius Joseph Mwanandota; Gilbert Msuta; Daniel Mdetele; Raphael Sallu; George Paul Omondi; Augustino Chengula; Sharadhuli Kimera; Satya Parida; Gerald Misinzo (Journal of Infection in Developing Countries)
Introduction: Peste des petits ruminants (PPR) is an infectious disease that imposes substantial economic burdens on small ruminants (SR) production. For Tanzania to develop efficient management and eradication plans, it is essential to comprehend the seroprevalence of PPR designated for global elimination by 2030.